INVESTIGATION OF GAP ADOPTION FOR CHILI GROWERS IN BAAN KAO SUBDISTRICT, SONGKLA PROVINCE, THAILAND (Proceedings of the International Conference on Agriculture, 2018)
It is generally required by imported countries that exported agricultural commodities must be complied with Good Agricultural Practices (GAP) standard prior to ensure safe consumption. Baan Kao subdistrict, Ranot district is the largest green chili cultivated area of Songkla province. More than 95% of green chili from this area is exported to Malaysia and Singapore. The number of GAP certified chili farms in the area is however less than 3%. To investigate such a low certified rate, a semi-structured questionnaire survey was conducted in early 2018. One hundred and ten out of one hundred and ninety five chili growing households answered the questionnaire. Ninety seven percent of growers are non-GAP certified. The main reasons for not pursuing GAP certification program are the lack of knowledge about benefit of the program for growers and the belief that participation as well as adoption is time-consuming. Perception and adoption of technologies required for GAP certification survey revealed that 4 technologies i.e. compost use, lime use for soil conditioning, diseased crops elimination, and 7-day pesticides withdrawal period were well perceived by more than 90% of responders. Only the 7-day withdrawal period was regularly practiced. Nevertheless, responders have good attitude toward minimization of pesticides use. This revealed data would have implication in strengthening agricultural extension program leading to safer chili farming practices.
Keywords: Green chili growers; Good Agricultural Practices; investigation